SUBJECTS AND POSITIONS IN THE DISCURSIVE ARENA OF THE «COAL REGION»: KUZBASS MEDIA DAILY OCCURRENCE - Alexandra E. Piskunova (Векторы благополучия: экономика и социум, 2022)
The article is devoted to the understanding of the Kuzbass media space. It forms a discursive environment defined by the dynamics of meanings, images, symbols that focus on the contextual interpretation of coal as a resource. The aim is to identify the mechanisms and contents of positioning processes in the regional media environment as discursive phenomena. Methodology: discursive approach to the analysis of the «coal region» media field. The focus is on how coal mining is discussed, what is said, who is speaking and who is absent from the media discourse. Results. The analysis of media facts made it possible to identify various actors in the community formed by the regional model of coal extractivism. Within the media field, they are involved in the communicative practices of contesting and (re)producing intersubjective semantic reality. On the one hand, it is a discursive coalition of the government and mining companies that mask the injustice and violence inherent in the logic of resource extractivism with the rhetoric of coal as a «common good». On the other hand, there are the voices of «experts» who make judgments about the ecological, economic and social conditions of the region, indigenous peoples and local communities directly affected by the impact of coal mining, and the «majority» voice, which fluctuates between different positions due to political and economic loyalty and dependence on the coal industry. It is noted that special discursive effects, power dispositions and cultural plots are deeply embedded in the socio-cultural reality of Kuzbass, in which coal, as a specific regional symbolic substance, exists as a source of meaning generation.